Analysis of the impact of exhaust gas emissions on diesel fueled vehicles in view from the year of manufacture (Case study on the Mitsubishi L 300 vehicle) - Irfan Dwi Farilla; Ali Akbar; Mulyadi; Rachmat Firdaus (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2024)
Air pollution is a condition caused by exhaust gas from motor vehicles operating on the highway. To minimize greater air pollution, the government is making preventive efforts by carrying out regular vehicle emission tests which are currently being carried out targeting transport vehicles. This is triggered by the increasing development of the automotive industry so that every year manufacturers produce these vehicles to meet the vehicle market, especially transport vehicle. With the increase in the number of vehicles every year, this is one of the causes of air pollution, so it needs to be controlled. This research aims to determine the effect of vehicle exhaust emissions on the year of vehicle production, in diesel fueled vehicles. The method used is an experiment using two-way Anova analysis on the results of tests carried out on Mitsubhisi L 300 vehicles with a total of 30 test samples, by testing vehicles produced in 2017 - 2022. The results of the research show that older vehicles will produce gas emissions. tall one. This is in accordance with the results of the ANOVA test which accepts the statement that there is at least one vehicle age that has a significant effect on smoke concentration, so it can be concluded that vehicles with an old age, in this case 2017, have the potential to produce high emission gases, therefore preventive efforts need to be taken. to vehicle engines